Chemical composition of marandu palisade grass fertilized with nitrogen and potassium - K. C. Sales; J. G. Abreu; C. E. A. Cabral; A. Behling Neto; L. C. R. P. Silva; I. M. Silva Neto (Boletim de Indústria Animal)
The goal was to evaluate the chemical composition of Urochloa brizantha cv. Marandu through the use of fertilization with nitrogen and potassium. The experiment was carried out at the Experimental Farm of UFMT, Cuiabá Campus, from December to April 2017/2018 and 2018/2019 - rainy season; and from May to September in 2018 and 2019 – dry season. Treatments corresponded to a 5x2 factorial scheme, with five nitrogen doses (0; 25; 50; 75; 100 kg ha-¹) and two potassium doses (0; 25 kg ha-1). The sample was unified as one for each individual period. The chemical characteristics evaluated were crude protein (CP), mineral matter (MM), neutral detergent fiber (NDF), acid detergent fiber (ADF), indigestible neutral detergent fiber (iNDF), total digestible nutrients (TDN) and net energy of lactation (NEF). For CP, a positive linear effect was observed for nitrogen fertilization, with 15.87% and 11.68% for the highest dose in the rainy and dry seasons, respectively. Likewise, a linear increase in TDN and in NEL was observed. For NDF, ADF and iNDF content there was a linear reduction in both rainy and dry seasons. For potassium fertilization, there is little influence on the chemical characteristics, in fact, only in the rainy season for fiber, TDN and NEL contents. However, nitrogen fertilization promoted an increase of 51.13% in the CP content at the highest applied dose. The NDE, ADF and iNDF content decrease linearly with nitrogen input, on the contrary, there was an increase in TDN and NEL.